Meningkatkan Keterampilan Menulis Karangan Deskriptif dengan Menggunakan Media Gambar Pada Mata Pelajaran Bahasa Indonesia Kelas IV SDN 2 Sangkanwangi Lebak Banten - Dion Dista; Ratna Dewi; Rifki Arif Nugraha (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
ABSTRACT Dion Dista, Improving Descriptive Essay Writing Skills Using Picture Media in Indonesian Class IV Subject at SDN 2 Sangkanwangi Lebak Banten. Thesis, Undergraduate Study Program in Elementary School Teacher Education, Syekh Manshur College of Teacher Training and Education 2021. This study aims to improve the process of learning to write Deskirpitf essays by using image media for fourth grade students at SDN 2 Sangkanwangi. This type of research is classroom action research. The research subjects were fourth grade students at SDN 2 Sangkanwangi for the 2023/2024 academic year with a total of 27 students. Retrieval of data using observation, tests, and interviews. The data collection tools used were observation sheets, test sheets, and interview guides. Analysis of research data using a mixture. The results showed that the process of learning to write descriptive essays has increased. This can be increased in a way; the teacher provides apperception and motivation, gives explanations to students about descriptive essays, shows media images, explores students' prior knowledge by asking and answering questions related to pictures, explains pictures, provides guidance to students, and provides an evaluation of writing descriptive essays. This increase can be seen from the seriousness of students in learning to write descriptive essays, enthusiasm in expressing their ideas, high enthusiasm/interest in writing descriptive essays, actively participating in discussions, feeling motivated, interested and competing with each other in writing descriptive essays. Descriptive essay writing skills also showed improvement. This can be increased in a way; Students observe pictures, explore their prior knowledge of pictures, write words that match the pictures and develop their ideas into descriptive essays as a whole by paying attention to the elements of the essay. The improvement in the skills of writing descriptive essays can be seen from the students' average scores increasing from the initial condition with the sufficient category (58.08) to the sufficient category (66.87) in cycle I and in cycle II to (80.02) the good category. Keywords "Skills, writing descriptive essays, media images”